Association between dynamic dose increases of buprenorphine for treatment of opioid use disorder and risk of relapse. (1st October 2021) - Rudolph, Kara E.; Shulman, Matisyahu; Fishman, Marc; Díaz, Iván; Rotrosen, John; Nunes, Edward V.
Abstract: Background and Aims: Dynamic, adaptive pharmacologic treatment for opioid use disorder (OUD) has been previously recommended over static dosing to prevent relapse, and is aligned with personalized medicine. However, there has been no quantitative evidence demonstrating its advantage. Our objective was to estimate the extent to which a hypothetical intervention that increased buprenorphine dose in response to opioid use would affect risk of relapse over 24 weeks of follow‐up. Design: A secondary analysis of the buprenorphine arm of an open‐label randomized controlled 24‐week comparative effectiveness trial, 2014–17. Setting: Eight community addiction treatment programs in the United States. Participants: English‐speaking adults with DSM‐5 OUD, recruited during inpatient admission ( n  = 270). Participants were mainly white (65%) and male (72%). Intervention(s): Participants were treated with daily sublingual buprenorphine–naloxone (BUP–NX), with dose based on clinical indication, determined by the provider. We examined a hypothetical intervention of increasing dose in response to opioid use. Measurements: Outcome was relapse to regular opioid use during the 24 weeks of outpatient treatment, assessed in a survival framework. We estimated the relapse‐free survival curves of participants under a hypothetical (i.e. counterfactual) intervention in which their BUP–NX dosage would be increased following their own subject‐specific opioid use during the first 12 weeks of treatment versus a hypothetical intervention in which dose would remain constant. Findings: We estimated that increasing BUP–NX dose in response to recent opioid use would lower risk of relapse by 19.17 percentage points [95% confidence interval (CI) = −32.17, −6.18) (additive risk)] and 32% (0.68, 95% CI = 0.49, 0.86) (relative risk). The number‐needed‐to‐treat with this intervention to prevent a single relapse is 6. Conclusions: In people with opioid use disorder, a hypothetical intervention that increases sublingual buprenorphine–naloxone dose in response to opioid use during the first 12 weeks of treatment appears to reduce risk of relapse over 24 weeks, compared with holding the dose constant after week 2.